ANALISIS PENDAPATANUSAHATANI KELAPA SAWIT DI DESA LILIMORI KECAMATAN BULUTABA KABUPATEN MAMUJU UTARA - Marzuki, Marzuki; Hadayani, Hadayani (AGROTEKBIS, 2019)
The objective of this research is to find out the farmers income of palm oil farm in Lilimori village of Bulutaba Subdistrict of North Mamuju Regency. The research was conducted from May to July 2017. The sample was 31 respondents of palm oil farmers. The analysis method used income analysis research. The result of this research showed that the production income was 11,322,580 kg/2.38 ha/2 months or 4,757,386 kg/ha/2 months, the price of per kilogram was IDR 1,100, so that the revenue was IDR 12,454,838/2.38ha/2 months. Total cost was IDR. 5,608,354/2ha/2 months or 2.356.451/ha/two months, so the income earned by palm oil farmers in lilimori village was IDR 6,846,484/2.38ha/2 months or 2,876,674/ha/2 months.